CMIP5 multimodel projections of extreme weather events in the humid subtropical Gangetic Plain region of India. Issue 2 (23rd February 2017) - Nath, Reshmita; Cui, Xuefeng; Nath, Debashis; Graf, Hans F.; Chen, Wen; Wang, Lin; Gong, Hainan; Li, Qian
Abstract: Since 1960s, India experiences a series of extreme drought and flood events during the summer months. The Humid Subtropical Climatic Zone (HSTC), which comprises the Indo‐Gangetic Plain region of India, is highly vulnerable to the climatic extremities. This region is the home for approximately 40% of total population and yields approximately 50% of total agricultural production of India. We investigate the historical variation in dry/wet conditions and project the future changes in extreme events under two different scenarios of the Coupled Model Inter‐comparison Project 5 models. First, the model parameters, that is, precipitation ( P ) and temperature ( T ) are bias corrected with respect to observation data and finally six models are selected, which are in right phase with the observation for composite analysis. Next, we calculate the potential evapotranspiration (PET) and the Standardized Potential Evapotranspiration Index to characterize the extreme events. Both P and PET are projected to increase in the HSTC zone; however, both the wet and dry conditions demonstrate a persistent increase in future. In relative terms, P increases faster than PET along the Gangetic Plain region (wet condition) and decreases in the southern and eastern part of the region (dry condition). The mitigating effect (RCP4.5 scenario) of precipitation increase will be overridden by strengthened PET and extreme dry condition project markedly under RCP8.5 scenario. The features are consistent with the increase/ decrease in multimodel mean SPEI, consistent with the spatial pattern of P −PET. The area affected due to wet and dry events will be relatively higher under the RCP4.5 and RCP8.5 scenario, respectively. Key Points: CMIP5 model bias correction and select models in phase with observation for composite analysis Future projection of extreme weather events over humid subtropical Gangetic Plain in two scenarios Both extreme wet and dry conditions are projected to increase in future under global warming